Apakah Nasab Merupakan Syarat Kafa’ah dalam Pernikahan - Nilam Khansa; Juita Sari Harahap; Rahmadani Fauza Harahap (STIKes Ibnu Sina Ajibarang, 2025)
A balanced relationship that exists between men and women or kafa'ah, is necessary for marital satisfaction. Because many people want to have sons-in-law from good descendants, the nasab kafa'ah is used in marriages between men and women. Regarding marriage, how do the majority of the ulama respond to the nasab? how do the ulama react to the kafa'ah nasab in this marriage. The research methodology used in this study is library research. This research uses descriptive analysis, namely a methodology that uses data to explain and analyze problems using factual information. Regarding lineage (ancestry) as a criterion for kafa'ah, scholars have different opinions. The majority of scholars use lineage as a criterion for kafa'ah; according to this perspective, nen Arabs are not equal to Arabs. Scholars use nasab, or lineage as a criterion in kafa'ah according to this perspective, non-Arabs are not equal to Arabs.